Optimizing Stony Coral Tissue Loss Disease (SCTLD) Intervention Treatments on Montastraea cavernosa in an Endemic Zone - Walker, Brian K.; Turner, Nicholas R.; Noren, Hunter K. G.; Buckley, Samantha F.; Pitts, Kelly A. (Frontiers in Marine Science, 2021)
Stony coral tissue loss disease (SCTLD) has persisted since 2014 in the Southeast Florida Coral Reef Ecosystem Conservation Area (Coral ECA) where it was first discovered. Most of the highly susceptible corals have perished, leaving Montastraea cavernosa as the most abundant reef-building species with high SCTLD prevalence. Disease interventions (DI) have been conducted throughout Florida’s Coral Reef to save the remaining corals and reduce the disease prevalence with varying degrees of success. The two main treatments were chlorinated (Chl) epoxy and an antibiotic paste. The antibiotic paste was highly effective in the Florida Keys, but its effectiveness in the Coral ECA was questionable. Therefore, we compared the effectiveness of the antibiotic paste and Chl epoxy treatments on M. cavernosa to optimize DI efforts on this species in the Coral ECA. Significant differences were found between the treatment materials and applications related to the proportion of quiesced lesions and corals where antibiotic paste (91.2% success) outperformed Chl epoxy (20% success). By day 351, 50.6% of the antibiotic paste disease-break tissue was fully healed compared to 2.2% of the total Chl epoxy-filled disease-break area. During the study, new lesions occurred on previously treated colonies, as well as colonies not previously treated and new lesion rates varied through time, indicating revisitation is necessary to eliminate disease. Most margin treatments failed within the first 9 days, however, most disease-breaks failed before 44 days. Considering the high treatment success of the antibiotic paste and the conditional variation of new lesion rates, about 1 month is a good practical re-visitation time for retreating failures and any new lesions. DI using antibiotic paste is currently the most effective way to intervene the SCTLD epidemic, but this is only effective as a stopgap measure while the larger causative agents are identified and remediated. Conducting DI at a reef-scape scale is time consuming and requires extensive person-power and resources, making it very expensive. But this expense pales in comparison to the current cost to restore the diversity and live tissue saved with DI. This method also comes with the risk of introducing antibiotics into coral reef environments, which may have unintended outcomes.